Pengaruh Kepatuhan Konsumsi Tablet Tambah Darah Terhadap Kejadian Anemia Pada Remaja Putri Di SMK 01 Tanjung Palas - Febriyanti Dwi Saputri (Lembaga Publikasi Ilmiah Nusantara, 2023)
The prevalence of anemia in the teenager group ages 15-24 years by 32% which means 3-4 out of 10 teenagers suffer from anemia, on 2018, riskesdas data showed that 100% youth women in Indonesia there are 76.2% of teenagers daughter who got TTD at school And obtained 80.9 % consumed iron tablets and 19.1% did not consume TDD. So the Indonesian government did intensification the prevention And management of anemia in rheumatism and WUS with prioritized administration of TTD through institutional schools. Type study This is a pre-experimental design with the use design study form a one-group case study research design, population is Rematri SMK 01 Tanjung Palas with sample 43 rematri with technique taking Probability sampling with sampling technique random sampling. The results of this study showed that there was no effect of compliance with iron supplement consumption on the incidence of anemia in adolescents at SMK 01 Tanjung Palas (Asymp. Sig = 0.196 > 0.05). The incidence of anemia in rheumatism Can be lowered with the consumption of TTD each Sunday will but needed obedience in consumption of the iron substance, role from the environment especially teachers and power health very needed in increasing obedience to TDD consumption. Adherence to iron supplements consumption by teenagers can be caused by many factors, factors from themselves and the environment such as teacher support is a trigger for teenagers to consume iron tablets every 1 week.